Quartieris to celebrate anniversary (Raton, New Mexico Raton Range, 1985)
Newspaper Article on the 50th Anniversary of Lino and Virgie Quartieri.
Master list item #: 16
File location is in the Raton File Cabinet
Keywords: Quartieri, Lino; Quartieri, Virgie; Hutchens, Joyce; Quartieri, Ronnie; Quartieri, David; Lytle, Mary; Quartieri, Lawrence; Winchell, Dora; Pompeo, Maya; Polombo, Sylvia; Maxwell Club Rooms; Biography; Local History; Life and Customs; Marriage; Celebration; Anniversary; Raton, New Mexico; Maxwell, New Mexico; Farmington, New Mexico; Los Alamos, New Mexico; Germeny; El Reno, Oklahoma; Denver, Colorado